SHAHIFAH MADINAH DALAM KAJIAN HADIS - Hemawati, Hemawati; Budi, Abdullah; Dian, Anggraini (Jurnal Generasi Tarbiyah: Jurnal Pendidikan Islam, 2022)
The Sahifah of Medina is a text of an agreement that was drawn up by the Prophet Muhammad with the people of Medina which took place around the first year of Hijriyah, but there are also those who say that the event occurred in the 2nd century Hijri on the grounds that it was in the first year of the Hijriyah of the Prophet Muhammad. just moved in and need to prepare everything including the place to live. Regarding the validity of the sahifah madinah text which is still doubted by some experts, because everything said, done and approved by the prophet is recognized as a hadith, of course the madinah shahifah is considered a hadith. Regarding the uncertainty of the occurrence of the agreement and regarding the existence of the manuscript, this is the basis and reason for conducting this research, so it is necessary to study the hadith to find out its existence. The purpose of this study was to determine the validity of the sahifah madinah manuscript in the hadith. The approach is taken using a library approach by conducting a search on the hadith about the sahifah madinah text in the books of hadith. The results showed that: not found in the books of hadith, and the scholars recognized the Sahifah of Medina and as an agreement to live together in Medina.